Self-loading suspension rack for production storage & delivery of precast components / Izanie Nur Athira Ibrahim and Azamudin Husin - Ibrahim, Izanie Nur Athira; Husin, Azamudin (2019)
Industrial Building System (IBS) bring forward the conventional method of construction to new modern installation of building components that were previously casted off-site. This technique does bring advantages such as cut of cost, time and enhance quality. However, regardless of IBS's advantages, it does have some critics, certain weakness that lead to misperception in construction society. Things goes worse, if IBS being conducted in a wrong way or disguise the standard of operation. These were usually done by worker or particularly categorized as gross error. These can lead to product defects, and most commonly cause is crack. To solve this problem, a self-loading suspension rack (SLSR) is proposed with aim to minimize material handling and human interference which generally helps to avoid defects such cracks. SLSR shall be created with merging concept of suspension system with innovation of automation moving rack. The nature of precast concrete construction entails thorough preconstruction planning. As the various aspects and phases of the project are interrelated, its success will depend largely on how effective is the linkage between each construction phase during implementation. Construction sequences, production storage and delivery process are therefore important and need to be closely monitored to obviate costly double handling such rectification work in site progress.